Um estudo descritivo-analítico do Compendio da Grammatica da Lingua Nacional de Antônio Álvares Pereira Coruja - Medeiros, Juliana Borges de (2017)
Our thesis is related to the area of research of History and Description of the Portuguese Language. It aims at focusing on Antônio Álvares Pereira Coruja’s Compendio da Grammatica da Lingua Nacional, whose subject area refers to contextual movements within the production of such work. The main goal of our research is to go over Coruja´s Compendio, in order to make a contribution to a better understanding of Brazil´s early grammar production, going back to 19th century's first half, namely (1) to describe the political, social, economic, cultural and educational scenarios of the author's most intense writing period, and (2) to analyze the Compendio. The relevance of our research is justified by the author's outstanding position in our country's grammar history, since he had the merit of coming up with our grammaticography (Nascentes, 1939). Our work was based on the theory presented in History of Linguistic Ideas, a course which analyzes the ways in which linguistic knowledge has been interpreted and developed throughout history. We used the theoretical-descriptive and deductive methodological procedure and all steps taken proved effective in search of explanations of the goals hereby presented